Les fibules discoïdes à décor de « monstre » regardant en arrière (ixe-xe siècle) découvertes en France - Jean Soulat (Archéologie Médiévale)
The purpose of this article is to highlight a particular brooch type dating from the Carolingian period, disc brooches decorated with “a monster” known to British archaeologists as backward-looking animal brooches. These early tenth-century brooches have been discovered in large numbers in England but only sporadically on the continent, including on six occasions in France. In conjunction with the inventory of these few examples, and using the best comparable finds from elsewhere, iconographical heritage and stylistic influence are considered in order to better our understanding of these little-known ornaments.